Issues related to pathological diagnostic criteria for N-staging in colorectal cancer - Ni Xiang; Jiang Yingjie; Bai Chenguang (结直肠肛门外科)
Accurate pathological TNM staging of colorectal cancer is of great significance in developing clinical treatment plans. However, some new issues have arisen in the pathological assessment of N-staging, i.e., lymph node metastasis, including the interpretation and clinical application of tumor deposits, the recognition of lymph node capsular invasion, and the assessment of treatment response in positive lymph nodes in specimens from neoadjuvant therapy. This article briefly reviews the above-mentioned issues to facilitate discussions with colleagues.